Modeling the Dynamics of Multispecies Fisheries: A Case Study in the Coastal Water of North Yellow Sea, China - Wo, Jia; Zhang, Chongliang; Pan, Xindong; Xu, Binduo; Xue, Ying; Ren, Yiping (Frontiers in Marine Science, 2020)
Ecosystem models have been developed for detecting community responses to fishing pressure and have been widely applied to predict the ecological effects of fisheries management. Key challenges of ecosystem modelling lie in the insufficient quantity and quality of data, which is unfortunately common in the marine ecosystems of many developing countries. In this study, we aim to model the dynamics of multispecies fisheries under data-limited circumstances, using a multispecies size-spectrum model (MSSM) implemented in the coastal ecosystem of North Yellow Sea, China. To make most of available data, we incorporated a range of data-limited methods for estimating the life-history parameters, and conducted model validation according to empirical data. Additionally, sensitivity analyses were conducted to evaluate the impacts of input parameters on model predictions regarding the uncertainty of data and estimating methods. Our results showed that MSSM could provide reasonable predictions of community size spectra and appropriately reflect the community composition in the studied area, whereas the predictions of fisheries yields were biased for certain species. Errors in recruitment parameters were most influential on the prediction of species abundance, and errors in fishing efforts substantially affected community-level indicators. This study built a framework to integrate parameter estimation, model validation, and sensitivity analyses altogether, which could guide model development in similar mixed and data-limited fisheries and promote the use of size-spectrum model for ecosystem-based fisheries management.